MAINTENANCE STRATEGY BASED ON RELIABILITY: CASE STUDY OF A COMPANY IN THE ELECTRIC SECTOR - de Oliveira, Mauro Macedo; de Oliveira, Priscila Maria Ferreira (Revista Latino-Americana de Inovação e Engenharia de Produção, 2023)
In the electrical system, it is essential that the equipment remains in good condition in order to guarantee the energy supply and its continuity. Among these pieces of equipment are the circuit reclosers, which are tele-controlled devices that act on temporary faults, reducing the affected area in an occasional network failure and the time needed to restore the supply. Thus, the goal of this article is to propose a strategy based on Reliability-Centered Maintenance (RCM) for circuit reclosers used by an electric energy distributor in the Triângulo Crajubar, region localized in the countryside of Ceará – Brazil. Therefore, data related to time to failure, between failures, and until repair, was collected through the distribution company’s management system and with the help of the application Proconf 2000©, it was possible to determine the reliability functions, availability and current reliability of the devices. In addition, through the risk functions, it was determined the stage in the life cycle in which the reclosers were found, making it possible to verify the best maintenance strategy in each case, according to the literature. Then, it was concluded that the most adequate maintenance strategy to reclosers is preventive maintenance at predetermined intervals.